2023
DOI: 10.3390/jrfm16010030
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management in Practice: A Multiple Case Study Analysis in Italian Municipalities

Abstract: This paper aims to analyse the ways in which risk management has been embedded in management control systems in Italian municipalities. Through a qualitative method, this study presents multiple case studies from six municipalities with two levels of analysis: content analysis on the information published on the institutional website, and interviews through a questionnaire with open and closed questions addressed to the public managers of the Italian municipalities selected. Moreover, the municipality responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The contingency theory of leadership suggests that contingency buffers are set up to cover for project risk that may hinder project performance especially in situations of diverse events or anticipated threats (Zheng, Feng, Xie, Zhao, & Wu, 2023). The contingency theory posits that there is a need to create a linkage between risk management and performance management, moving towards integrated risk management (Castellini & Riso, 2023). Therefore, the contingency theory helps in understanding the influence of risk identification and risk analysis on the performance of road construction projects in Kilifi County, Kenya.…”
Section: Contingency Theorymentioning
confidence: 99%
“…The contingency theory of leadership suggests that contingency buffers are set up to cover for project risk that may hinder project performance especially in situations of diverse events or anticipated threats (Zheng, Feng, Xie, Zhao, & Wu, 2023). The contingency theory posits that there is a need to create a linkage between risk management and performance management, moving towards integrated risk management (Castellini & Riso, 2023). Therefore, the contingency theory helps in understanding the influence of risk identification and risk analysis on the performance of road construction projects in Kilifi County, Kenya.…”
Section: Contingency Theorymentioning
confidence: 99%
“…The contingency theory of leadership suggests that contingency buffers are set up to cover for project risk that may hinder project performance especially in situations of diverse events or anticipated threats (Zheng, Feng, Xie, Zhao, & Wu, 2023). The contingency theory posits that there is a need to create a linkage between risk management and performance management, moving towards integrated risk management (Castellini & Riso, 2023). Therefore, the contingency theory helps in understanding the influence of risk identification and risk analysis practices on the performance of mining projects in Kwale County, Kenya.…”
Section: Contingency Theorymentioning
confidence: 99%
“…In addition, although the definition of a management control system seems to also include risk assessment, public organizations rarely integrate risk management and management control systems (Bracci et al, 2020;Riso and Castellini, 2019;Arena et al, 2017). In addition, Castellini and Riso (2023) showed that in selected Italian municipalities, there is low integration between risk management and management control systems, and Riso et al (2022) showed that large Italian municipalities disclose information on their risks but not on risk management practices. Furthermore, Italian legislation addresses some specific risks (e.g.…”
Section: Research Contextmentioning
confidence: 99%
“…In particular, the legislative obligation to implement a management control system in public organizations with an internal auditor was introduced in 2000 (Legislative decree 267/2000). In 2012, law 190 introduced a framework to prevent the risk of corruption and illegality in public administrations (Castellini and Riso, 2023). However, no specific law obliges public organizations to implement risk management for all risks.…”
Section: Introductionmentioning
confidence: 99%